Dissecting the Human Response to Staphylococcus aureus Systemic Infections - Leuzzi, Rosanna; Bodini, Margherita; Thomsen, Isaac P.; Soldaini, Elisabetta; Bartolini, Erika; Muzzi, Alessandro; Clemente, Bruna; Galletti, Bruno; Manetti, Andrea Guido Oreste; Giovani, Cinzia; Censini, Stefano; Budroni, Sonia; et al. (Frontiers in Immunology, 2021)
Staphylococcus aureus is a common human commensal and the leading cause of diverse infections. To identify distinctive parameters associated with infection and colonization, we compared the immune and inflammatory responses of patients with a diagnosis of invasive S. aureus disease to healthy donors. We analysed the inflammatory responses founding a pattern of distinctive cytokines significantly higher in the patients with invasive disease. The measure of antibody levels revealed a wide antibody responsiveness from all subjects to most of the antigens, with significantly higher response for some antigens in the invasive patients compared to control. Moreover, functional antibodies against toxins distinctively associated with the invasive disease. Finally, we examined the genomic variability of isolates, showing no major differences in genetic distribution compared to a panel of representative strains. Overall, our study shows specific signatures of cytokines and functional antibodies in patients with different primary invasive diseases caused by S. aureus. These data provide insight into human responses towards invasive staphylococcal infections and are important for guiding the identification of novel preventive and therapeutic interventions against S. aureus